An assessment of the competitiveness of Polish exports to Germany in respect of sectors based on market attractiveness and market position - Strojny, Jacek (Ocena konkurencyjności eksportu polskiego do Niemiec w ujęciu sektorowym na podstawie koncepcji atrakcyjności rynku i pozycji rynkowej, 2019)
The study is aimed at assessing international competitiveness of Polish exports on a selected market. The research was conducted at sectoral level. The research method employed is the attractiveness and position indicator (AP-indicator). The AP-indicator adopts the portfolio models approach. The method enabled to quantify target market’s attractiveness and the competitive position of Polish exports on that market. The research is based on EUROSTAT statistics and covers the period of 2010-2018. According to the results, all the widely defined categories of products delivered by Polish exporters to German may be considered as competitive. The most promising part of Polish exports on the considered market are the SITC 0+1, SITC 5, SITC 6+8, and SITC 7 class, characterised by the extraordinary market growth and high exports’ dynamics. The study is dedicated only to assessing competitiveness. Explaining the drivers of the competitiveness is beyond the scope of the research
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 245-257
Keywords: Polish exports; international competitiveness; AP-indicator; competitiveness indicator; polski eksport; konkurencyjność międzynarodowa; wskaźnik AP; miernik konkurencyjności